NOISE AND NATION: HOW IBEROAMERICAN ROCK REDEFINED THE SENSE OF COMMUNITY IN LATIN AMERICA - Garibaldo Valdéz, Ramón (2014)
This article traces how rock music evolved from a foreign cultural intrusion to a central element of regional identity in Latin America, overcoming early 20th-century national barriers. The key driver behind this shift was audio capitalism—the commercialization of cultural goods that ensured the economic viability of music. In the 1950s, only the upper class could access rock and roll, as it required international travel and purchasing power. Its foreign roots led to clashes with nationalist cultural projects, especially in Mexico, sometimes prompting state-backed repression. By the 1970s, various governments banned rock, pushing it into an underground scene where it nonetheless flourished. In the 1980s, rock re-emerged publicly, becoming a vehicle for the lower classes to voice their social and political grievances. It gradually transcended social divisions, becoming a multi-class form of expression. The launch of MTV Latino in 1993 symbolically erased national cultural frontiers for youth audiences, extending their cultural landscape to places like Brazil, Miami, and Spain. What began as elite entertainment in the 1950s, and was suppressed in the 1970s, ultimately became by the 1990s a transnational cultural platform through which a new Ibero-American youth identity was imagined and expressed.